Getting ethics into practice British Medical Journal (BMJ Publishing Group, 2004)
In their day-to-day practice, clinicians make not only scientific judgements about the effectiveness of one intervention in comparison with another, but also value judgements. Sometimes such judgements are explicit -for example, when a doctor reflects on his or her own moral views about the permissibility of abortion. In most cases however, value judgements in medical practice are implicit in what seem, at first glance, to be ‘clinical’ decisions.